Characteristics and Antioxidant Activity of Sweet Potato Syrup (Ipomea Batatas (L) with Propylene Glycol Variation - Elisma Elisma; Maria Y. Lenggu; Marce Inggritha Takubessi (JURNAL INFO KESEHATAN, 2020)
Sweet Potato Leaf (Ipomea Batatas (L) contains flavonoids and polyphenols which play a role in antioxidant activity. Sweet Potato leaf extract is formulated into syrup because it is faster to be absorption compared to solid preparations and more easily to swallow. Sweet potato extract is formulated with variations in the amount of propylene glycol which is 11% (F1), 12% (F2), 13% (F3) and 0% (control). The characteristics of syrup include organoleptic tests, viscosity tests and time of flow were determine and syrup antioxidant activity testing using method 2 , 2-diphenyl-1-picrylhydrazyl (DPPH). Test results showed that all formulas have the same organoleptic properties, which are brown, sweet and slightly bitter. Weak antioxidant activity showed by IC50 and AAI values. IC50 and AAI syrup were 134 ± 19.28, 128 ± 4.04, 115 ± 13.07, and 142 ± 1.5 mg / mL and the AAI values ​​were 0.074, 0.078, 0.087 and 0.070, respectively for F1, F2, F3 and control. Statistical analysis with the Kruskal-Wallis test (p> 0.05) showed no significant IC50 differences for the three formulas and control. The increase in propylene glycol affects the viscosity and ease of pouring but not the organoleptic properties while the antioxidant activity is not significantly different from the increase in propylene glycol. It is recommended to do a hedonic test for all three formulas in further research.